ANALISIS KEMAMPUAN BERPIKIR REFLEKTIF TERHADAP PEMAHAMAN IPA DALAM MENYELESAIKAN MASALAH PADA SISWA KELAS 5 DI SEKOLAH DASAR - Imam Suharso; Anita Kastur; Nurul Indah S; Fitria Hidayati; Endah Rahmawati; Julianto Julianto (Primary School Teacher Education, Universitas Nahdlatul Ulama Sidoarjo, 2026)
This study aims to analyze reflective thinking skills in relation to science (IPA) comprehension in problem-solving among fifth-grade elementary school students. The background of the study is the students' low ability to connect science concepts with real-life experiences, as well as the lack of habitual reflection during the learning process. A descriptive qualitative approach was employed, with data collected through questionnaires, interviews, and observations. The research subjects included students and teachers from three elementary schools in Surabaya: SDN Babatan, SDN Karangpilang, and SDN Wonocolo. The findings indicate that students’ reflective thinking skills are at a moderate level. Students who actively engage in hands-on practice and group discussions tend to demonstrate stronger reflective thinking. However, several obstacles were identified, such as low interest in reading, limited teacher strategies for implementing reflective learning, and the diversity of student characteristics that influence their learning responses. Therefore, science learning should adopt a more contextual, participatory, and experience-based approach to support the development of students' reflective thinking skills effectively